Menuju Peradilan yang Independen dan Akuntabel - Prastopo Prastopo; Agustinus Purnomo Hadi; Tiarsen Buaton; M. Ali Ridho; Ateng Karsoma; Mulyono Mulyono (Jurnal Studi Multidisiplin Ilmu, 2024)
Purpose: This paper will discuss the position and function of the judicial power in Indonesia, as seen from its development since 1959, when Indonesia returned to the 1945 Constitution until 2008. Thus this paper will look at the entirety of the legislation governing the judicial power since the return to the 1945 Constitution through the Presidential Decree of July 5, 1959 and towards a one-stop judiciary under the Supreme Court. The study will primarily be directed at how to make the judiciary in Indonesia more independent and accountable. Method: Examine legal literature, policies, and case studies related to judicial independence and accountability. Results: Identify key issues affecting the independence and accountability of the judicial system.